The Effectiveness of Kenikir Extract (Cosmos Caudatus) To Increase The Hormone Prolactin In Puerperal Mothers - Hidayah, Khoirotul; Suwondo, Ari; Kusmiyati, Yuni (Green Publisher Indonesia, 2023)
Failure of exclusive breastfeeding still occurs due to insufficient milk production. Kenikir or Cosmos Caudatus has active compounds that may increase breast milk, but there has been no further research on kenikir in breast milk production. Analyzing the effectiveness of kenikir extract in increasing prolactin hormone levels in puerperal mothers. This type of research is a true experiment with pretest posttest control group design. The independent variable is nikir extract. The dependent variable is the hormone prolactin. The sample of 40 postpartum mothers was divided into 20 mothers in the control group and 20 mothers in the intervention group. The analysis used the Paired T Test and Wilcoxon to determine the differences before and after the intervention in each group. Then Mann Whitney's analysis was carried out on differences between groups. Administration of 300 mg of kenikir extract for 14 days can increase the hormone prolactin with an average of 44.70 ng / ml p value 0.0001. Giving kenikir extract is effective in increasing the hormone prolactin in postpartum mothers.